Potensi Pasar Pupuk Organik Masyarakat Perkotaan di Gorontalo: Tinjauan Aspek Pengetahuan dan Perilaku - Nurdin Nurdin; Agustinus Moonti; Siswatiana R. Taha; Echan Adam; Rival Rahman (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This research aims to describe changes in the use of organic fertilizers in urban communities, both from the point of view of knowledge and behavior. This research was conducted in the period from February to April 2022. The population is urban in Gorontalo Province, with a random sample of 172 people with various professional characteristics. The research variables include people's perceptions, knowledge, and behavior regarding using organic fertilizers. Data were analyzed using descriptive statistics. The results showed that 95.3% of the urban community's perception of a suitable type of fertilizer chose organic fertilizer over non-organic fertilizer, and from the aspect of knowledge, as much as 69.8% knew the benefits of using organic fertilizer, both for plants and the environment and economic benefits. From the behavioral aspect, 83.7% of people are used to using organic fertilizers, and 62.8% prefer to use organic fertilizers compared to other fertilizers. The market potential for organic fertilizer for urban communities in Gorontalo Province based on aspects of knowledge and behavior is relatively high so that marketing can target urban communities. Communities can use agricultural shops with good reputations or images to obtain or trade organic fertilizers.